2014
DOI: 10.23986/afsci.9489
|View full text |Cite
|
Sign up to set email alerts
|

Changes in content of major phenolic compounds during leaf development of sea buckthorn (Hippophaë rhamnoides L.)

Abstract: Content of total phenolic compounds and antioxidant capacity (FRAP) were investigated in the leaves of three sea buckthorn (Hippophaë rhamnoides L.) cultivars: 'Otradnaja', 'Gibrid Pertjika' and 'Ljubitelskaja', at different dates. In addition, major phenolic compounds (catechin, kaempferol, quercetin, epigallocatechin, kaempferol-3-O-glucoside, quercetin-3-O-galactoside, isorhamnetin-3-O-glucoside, rutin, gallic acid, procyanidin monomer glycoside, procyanidin dimer aglycone and hydrolyzable tannins I-III) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…It was lower than the range of 82% to 96% FW in most vegetables (lettuce, green beans, asparagus, green peppers, and spinach) reported by Granado et al (1992), but comparable with that (67% FW) of tea leaf (Li et al, 2012). Morgenstern et al (2014) found the highest DW content in leaves of sea-buckthorn collected at the end of July (32%). Our analysis did not distinguish a variety of sea-buckthorn that differs significantly in DW content in the dried leaves (p ≤ 0.05).…”
Section: Resultsmentioning
confidence: 83%
“…It was lower than the range of 82% to 96% FW in most vegetables (lettuce, green beans, asparagus, green peppers, and spinach) reported by Granado et al (1992), but comparable with that (67% FW) of tea leaf (Li et al, 2012). Morgenstern et al (2014) found the highest DW content in leaves of sea-buckthorn collected at the end of July (32%). Our analysis did not distinguish a variety of sea-buckthorn that differs significantly in DW content in the dried leaves (p ≤ 0.05).…”
Section: Resultsmentioning
confidence: 83%
“…The principal components of tannin fraction present in leaves are hydrolysable gallo-and ellagi-tannins of monomeric type [6]. The major phenolic compounds in HL are: hydrolysable tannins I-III, catechin, kaempherol, quercetin, epigallocatechin, kampherol-3-O-glycoside and procianidin dimer aglycone [9]. Amongst the phenolic compounds in HL, those in highest concentrations are hydrolysable (HT) and condensed (CT) (proanthocyanidins) tannins, the concentrations of which depend on cultivars and season [9].…”
Section: Introductionmentioning
confidence: 99%
“…The major phenolic compounds in HL are: hydrolysable tannins I-III, catechin, kaempherol, quercetin, epigallocatechin, kampherol-3-O-glycoside and procianidin dimer aglycone [9]. Amongst the phenolic compounds in HL, those in highest concentrations are hydrolysable (HT) and condensed (CT) (proanthocyanidins) tannins, the concentrations of which depend on cultivars and season [9]. The HL extracts are rich in medically active compounds -flavonoids, tannins, quercetine derivates and triterpenes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of several berry species, such as sea buckthorn ( Hippophae rhamnoides ) (SBT) and black currant ( Ribes nigrum ), have e.g. been shown to be rich in antioxidant compounds ( Morgenstern et al, 2014 , Vagiri et al, 2015 ). Onion ( Allium cepa ) peel and outer layers (skin) are typically removed and discarded in industrial food production although these waste materials might have high antioxidant properties as well ( Gawlik-Dziki et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%